(untitled) (Transactions on Additive Manufacturing Meets Medicine, 2024)
Designing encapsulations for medical implants with integrated electronics is very challenging because a solution for several different and partly opposing requirements like biocompatibility, low water permeability, mechanical stability and small dimensions has to be found. This work focusses on epoxy encapsulations, which are conventionally cast using silicone molds. For making these molds, a pattern has to be CNC machined and the silicone mold has to be cast from it. In this paper, a rapid prototyping method is proposed, which uses additively manufactured molds made by an inkjet 3D printer that operates with a silicone-based material. A proof of concept is presented for an electronic osteosynthesis implant, which is successfully encapsulated following the rapid prototyping method and compared to results obtained with the conventional method. The demonstrator was immersed in isotonic saline solution for three weeks without any negative effects on the functionality. The rapid prototyping approach required only 15% of the time needed by the conventional mold making process based on silicone casting and used less material. This shortens design cycles for the optimization of the encapsulation for electronic implants and enables to evaluate more design variations with little additional effort. Moreover, designs with more degrees of freedom are available in the additive manufacturing process. For casting the encapsulation, the same material as for the final implant can be used so that many properties like water permeability and mechanical stability can be evaluated in the early development phase.